CHARACTERISTICS OF OPEN ANGLE GLAUCOMA PATIENTS AT THE EYE POLYCLINIC PROF DR IGNG NGOERAH GENERAL HOSPITAL DENPASAR 2022 - Agrasidi, Putu Anindya; Suryaningrum, I Gusti Ayu Ratna; Kusumadjaja, I Made Agus (E-Jurnal Medika Udayana; Vol 13 No 6 (2024): E-Jurnal Medika Udayana, 2024)
Introduction : Open-angle glaucoma is a chronic, progressive, and irreversible multictorial optic neuropathy with open angle of the anterior chamber, accompanied by visual field disturbances, with increased intraocular pressure as the main risk factor, caused by trabecular meshworks resistance. The incidence of open-angle glaucoma is 2.4 million people each year. This study aims to determine the characteristics of open-angle glaucoma patients at the eve polyclinic Prof Dr IGNG Ngoerah Hospital Denpasar in 2022. Methods : This research is a descriptive analytical research with retrospective analysis. The study was conducted by collecting data based on observations of the medical records of patients who visited the Eye Polyclinic at Prof Ngoerah General Hospital in the period of January 1, 2022 until December 31, 2022. A total of 38 people (64 eyes) who met the inclusion and exclusion criteria were analysed using SPSS windows version 26.0. Results : The majority of subjects aged > 60 years (63.2%), male (68.4%). POAG (76.6%), SOAG (23.4%), the most common etiology of SOAG was lens induce, advanced stage (40.6%), and all had chronic onset. The median of visual acuity (logMar) pre operation vs three months post operation 1.0 vs 0.7, IOP 23 mmH vs 16 mmH, the mean of anti glaucoma medication was 1.37 vs 0.6. Conclusion : In patients with open-angle glaucoma, there is a good response to all treatment modalities (medical, trabeculectomy, phacoemulsification-IOL, phacoemulsification- IOL-trabeculectomy, implant glaucoma).